If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14c + -7 + -3 = 6 + 6c Reorder the terms: -7 + -3 + 14c = 6 + 6c Combine like terms: -7 + -3 = -10 -10 + 14c = 6 + 6c Solving -10 + 14c = 6 + 6c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-6c' to each side of the equation. -10 + 14c + -6c = 6 + 6c + -6c Combine like terms: 14c + -6c = 8c -10 + 8c = 6 + 6c + -6c Combine like terms: 6c + -6c = 0 -10 + 8c = 6 + 0 -10 + 8c = 6 Add '10' to each side of the equation. -10 + 10 + 8c = 6 + 10 Combine like terms: -10 + 10 = 0 0 + 8c = 6 + 10 8c = 6 + 10 Combine like terms: 6 + 10 = 16 8c = 16 Divide each side by '8'. c = 2 Simplifying c = 2
| y+8=-(x+8) | | 14s-8s-3=15 | | 14c=10+6c | | 1=9f+x | | y-10=3(x-3) | | 33=16m-12-m | | 19n+21=21 | | 5b=-1 | | -x^4-4x=0 | | y+4=8(x-2) | | 2-16t=-12t+12 | | 2.5-3.1t=21.05 | | https://hcps.blackboard.com/bbcswebdav/pid-1004819-dt-content-rid-2152875_1/xid-2152875_1 | | y-6=-8(x-4) | | 60-6b=-89 | | 130+.5x=40+.8x | | 9y-5-y=35 | | 12-2x=-2(y-x)-12 | | -12y=2x-3 | | 3(3x+1)+4=-23 | | 7.4x+1y=801900000 | | P=2.6x+33.0 | | 4x+2x+3x-3= | | 9x+6+x=46 | | 9x+7=-23 | | 3-4(5-7x)=5(2x+5)-2 | | y+8=-(x-9) | | 50-7y=-14 | | 100+.30x=70+.50x | | 10(.4+.5)=4g | | 66365/6=x | | 10(.04+.05g)=4g |